Uji Efektivitas Beberapa Konsentrasi Ekstrak Daun Kirinyuh (Chromolaena odorata L.) Terhadap Perkembangan Ulat Krop Kubis (Crocidolomia pavonana F.) - I NYOMAN WIJAYA; I GEDE PUTU WIRAWAN; WAYAN ADIARTAYASA (Agrotrop : Journal on Agriculture Science, 2018)
Effectiveness Test of Several Concentrations of Kirinyuh Leaf Extract (Chromolaena odorata L.) Toward Development of Cabbage Crop Caterpillar (Crocidolomia pavonana F.). This research was conducted at the Laboratory of Plant Pests and Diseases of the Faculty of Agriculture, Udayana University from April 2018 to August 2018 to test the extract of kirinyuh leaves (Chromolaena odorata) on the development of biology of cabbage crop caterpillar (Crocidolomia pavonana). The completely randomized design (CRD) was used in this study, with four types of treatment of leaf extract concentration of 10%, 20%, 30%, 40%, and control. Each treatment was repeated 10 times. Observations were completed every day of the larval stage until the larvae do not carry out any activity anymore (dead), or until they become imago. The results showed that (1) the leaf extract of C. odorata plant which was used as research material had the potential to suppress the biological development of C. pavonanadi larvae in the laboratory, (2) the application of leaf extract concentration of 10% and 20% had an influence on the development of larvae which had developed slow compared to concentrations of 30% and 40%, where larvae experience rapid development of only 9 observations and (3) the most effective test leaf extract treatment was the treatment of leaf extracts of C. odorata concentrations of 40% and 30% followed by leaf extract concentrations of 20% and 10%.